A numerical study on assessing sustainable development with future genuine savings simulation. (1st January 2012) - Sato, Masayuki; Samreth, Sovannroeun; Yamada, Katsunori
This paper presents a numerical examination of sustainability from the perspective of 'genuine savings', using a dataset provided by the World Bank. Unlike previously-used criteria of sustainability that focus on observed paths of genuine savings rates, we consider future sustainability by simulating future paths of genuine savings. This analysis shows that some countries that had been classified as being sustainable by previous studies, using observed paths, are in fact, not sustainable from the perspective of future sustainability. We provide information on capital components which should be targeted by policy makers in order to maintain future sustainability.